2018
DOI: 10.1155/2018/7623639
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Is an Independent Predictor of Multivessel Coronary Artery Disease in Young Adults with Acute Coronary Syndrome

Abstract: Background Risk factors of multivessel coronary artery disease (CAD) among young acute coronary syndrome (ACS) patients remain elusive now. Methods This retrospective study analyzed data from 187 consecutive young (age ≤45 years) ACS patients (75 STEMI, 30 NSTEMI, and 72 unstable angina) hospitalized in our hospital from January 2012 to December 2016. Thirty-six young male patients with normal coronary angiography (CAG) findings (no-CAD), who underwent CAG due to suspected chest pain in this period, served as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
4
16
1
1
Order By: Relevance
“…However, comparative data relating to subclinical characteristics in young ACS patients is still limited; some previous studies have shown different results, possibly due to differences in sample selection and anthropometry characteristics of research subjects. [ 16 , 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, comparative data relating to subclinical characteristics in young ACS patients is still limited; some previous studies have shown different results, possibly due to differences in sample selection and anthropometry characteristics of research subjects. [ 16 , 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…As regarding to admission diagnosis, 21% of our patients diagnosed as Non 128.6 ± 19.4 and the mean HR was 72.0 ± 14.4, this may be due to small sample size of our study [18].…”
Section: Discussionmentioning
confidence: 73%
“…Hypertension appeared to be the most prominent modifiable risk factor (54.71%) in our study and is consistent with the other studies. A study done in India by Mohanan et al(2013) 18 reported 48.8% hypertension in ACS patients while in another study done recently in China by Ge et al (2018) 19 have documented 57.2% patients of ACS with hypertension. Our study reported that both history of previous IHD and family history (37.65%) were same among all patient and these findings are almost in agreement with those of Ralapanawa et al (2019) 20 who carried out research on 300 ACS patients and investigated that previous history of IHD in patients and family history of IHD were 41% and 33% respectively.…”
Section: Resultsmentioning
confidence: 96%